(untitled) (Journal of Misan Researches, 2024)
The learners’ attitudes have a great affect on their consciousness and ability to learn. The high positive attitudes toward a certain strategy would results in creating effective learning process . The current study aims at investigating the students’ attitudes toward using the semantic translation strategy in English learning. The researcher chose a sample of thirty-five males and females’ students from English Department of Misan University as participants. To fulfill the goals of the study, a questionnaire was used. The outcome of the study reveals that the participants in the study have a positive attitude toward using the semantic Translation strategy to learn language skills. Based on the results of the analysis, the participants used semantic translation as a learning strategy to produce, comprehend and remember English. Furthermore, it has also been found that students rely steadily upon semantics translation in the process of learning and acquiring English as a foreign language.